PEMERIKSAAN KADAR KOLESTEROL PADA LANSIA DI KAMPUNG TUA TELUK MATA IKAN KELURAHAN SAMBAU KECAMATAN NONGSA RT 03 / RW 07 KOTA BATAM - Yenni Aryaneta; Melita Frisca Anjani (LPPM-Universitas Batam, 2024)
Cholesterol is one of the components in forming fat which consists of various components such as triglycerides, phospholipids, free fatty acids. Cholesterol functions to build cell walls or cell membranes in the body. Cholesterol is a substance produced by the liver and from saturated fat in food, if levels are too high it can cause coronary artery disease. This type of research is descriptive, namely to provide an overview of cholesterol levels in the blood of the elderly in Kampung Tua Teluk Mata Ikan, Sambau Village, Nongsa District Rt 03 / Rw 07. The method of collecting data is by using primary data obtained directly from the results of measuring cholesterol levels and then presented in table form to determine normal and abnormal conditions. After conducting research in Teluk Mata Ikan Old Village, Sambau Village, Nongsa District, Rt 03 / Rw 07 in March 2024, by checking cholesterol levels in the elderly and 24 people whose cholesterol levels had increased. It is recommended for elderly people who have high levels to regularly check their cholesterol levels at health facilities and reduce foods that are high in fat, and exercise regularly.